2021
DOI: 10.3389/fonc.2020.586029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of BRAF Inhibitors in Combination With Stereotactic Radiosurgery for the Treatment of Melanoma Brain Metastases: A Systematic Review and Meta-Analysis

Abstract: BackgroundBRAF inhibitors have improved the outcome for patients with BRAF mutant metastatic melanoma and have shown intracranial responses in melanoma brain metastases. Stereotactic radiosurgery (SRS) is being used as a local treatment for melanoma brain metastasis (MBM) with better local control and survival. We searched for studies comparing the combination of two treatments with SRS alone to detect any clinical evidence of synergism.Materials and MethodsPubMed, EMBASE, Medline, and Cochrane library were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 103 publications
1
10
0
Order By: Relevance
“…• PD-1 inhibitors improved survival, with more pronounced effect in patients not carrying the BRAF mutation • Among the patients treated with BRAFi, 10.4% developed intracerebral hematoma (ICH), in comparison to 3% of patients not treated with BRAFi (P = .03) melanoma brain metastases found that dual therapy of BRAF inhibitors in combination with SRS improved survival (P < 0.00001) and local control (P = 0.03), further supporting the literature of synergy between these two therapies (73).…”
Section: Melanomasupporting
confidence: 53%
See 1 more Smart Citation
“…• PD-1 inhibitors improved survival, with more pronounced effect in patients not carrying the BRAF mutation • Among the patients treated with BRAFi, 10.4% developed intracerebral hematoma (ICH), in comparison to 3% of patients not treated with BRAFi (P = .03) melanoma brain metastases found that dual therapy of BRAF inhibitors in combination with SRS improved survival (P < 0.00001) and local control (P = 0.03), further supporting the literature of synergy between these two therapies (73).…”
Section: Melanomasupporting
confidence: 53%
“…This study also illustrating that the timing of systemic therapy with relation to SRS delivery may affect clinical outcomes. Lastly, a 2021 meta-analysis including 8 studies and involving 976 patients with melanoma brain metastases found that dual therapy of BRAF inhibitors in combination with SRS improved survival (P < 0.00001) and local control (P = 0.03), further supporting the literature of synergy between these two therapies ( 73 ).…”
Section: Introductionmentioning
confidence: 69%
“…In a secondary analysis of the KEYNOTE-001 phase 1 trial, the benefit for NSCLC patients with previous radiotherapy receiving pembrolizumab was evident in terms of PFS (HR 0.56 [95% CI: 0.34, 0.91], p = 0.019) and OS (HR 0.58 [95% CI: 0.36, 0.94], p = 0.026) (49). In a metaanalysis of BRAF-mutant MBM patients, those administered BRAF inhibitors concurrently or after SRS induction showed superior benefit than patients receiving prior SRS (HR 0.39 [95% CI: 0.24, 0.65], p = 0.0003) (50). Similarly, in a retrospective study, MBM patients receiving BRAF inhibitor after SRS were noted to have better survival compared to those receiving BRAF inhibitors concurrently (24 months vs. 10.1 months, p = 0.007) (51).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the synergistic effect seen between BRAF inhibitors and SRS, the radiosensitizing effect of this drug class on melanoma cells plays an important role. This effect, originally seen in preclinical studies (131), has been validated in the clinical setting by pooled analyses which have shown a significant survival advantage with the combination of BRAFi and SRS compared to SRS alone (132). Combination therapy, however, carries the potential for increased toxicities such as the increased risk of radiation necrosis with ICI/SRS combination (133) and intracranial hemorrhage with BRAF inhibitor/SRS combination (132).…”
Section: Combined Local and Systemic Therapymentioning
confidence: 92%